Ecological significance of newly recorded halophilic Pharyngomonas kirbyi from two Korean solar salterns - Hyeon Been Lee; Jong Soo Park (Journal of Ecology and Environment)
Background: Hypersaline environments (> 40 practical salinity units [PSU]) represent some of the most extreme conditions on Earth, supporting a variety of halophilic and halotolerant bacteria, archaea, and protists. The taxon Heterolobosea includes numerous halophilic protists, making it a valuable model for studying eukaryotic adaptation to high salinity. Particularly, the genus Pharyngomonas, a deep-branching lineage within Heterolobosea, comprises mainly obligate halophiles, providing insights into early protist adaptations in hypersaline environments. Additionally, these protozoa play crucial ecological roles as grazers of bacteria and archaea, and are prey for higher trophic levels in hypersaline environments. Results: In the present study, two previously reported amoeboflagellates were isolated for the first time from hypersaline waters (~300 PSU) in two solar salterns in the Republic of Korea. Microscopic observations revealed that both strains exhibited the characteristic morphologies of Pharyngomonas, including amoeboid, flagellate, and cyst forms. Molecular phylogenetic analysis of their 18S rRNA gene sequences confirmed their close relationship to known Pharyngomonas kirbyi strains. The two strains demonstrated growth within a salinity range of 75–200 PSU, with optimal growth observed at 75–100 PSU, confirming their status as true halophiles. All known P. kirbyi strains are obligate halophiles, exhibiting a clear instance of adaptive radiation of halophilic eukaryotes. Additionally, the genus Pharyngomonas has been found in hypersaline environments across multiple continents (Asia, Europe, North America, Australia, and Africa), suggesting that it plays an ecologically significant role as a grazer of prokaryotes or prey for higher trophic levels in these habitats. Conclusions: On the bases of morphological and molecular analyses, two strains identified as P. kirbyi were isolated and characterized for the first time from solar salterns in the Republic of Korea. This discovery highlights the presence and adaptation of halophilic eukaryotes in such extreme environments. The confirmation of these strains as obligate halophiles provides additional evidence for the adaptive radiation of halophilic eukaryotes. Furthermore, the ecological role of Pharyngomonas species underscores their importance as trophic regulators in hypersaline ecosystems. These findings contribute to a deeper understanding of the diversity, adaptation, and ecological functions of halophilic eukaryotes in extreme environments.